2014
DOI: 10.1177/0306624x14522600
|View full text |Cite
|
Sign up to set email alerts
|

On the Potential Implications of Reports of Fictitious Drug Use for Survey Research on Juvenile Delinquency

Abstract: A variety of methodological issues have been raised over self-reports of delinquency and its correlates. In this study, we call attention to the provision of untruthful information and provide an investigation of this issue using a survey item that assesses a respondent's use of a fictitious drug in relation to reports of delinquency and traditional criminological correlates. Bivariate and multivariate analyses were conducted based on data drawn from a probability sample of middle and high school students in F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
(24 reference statements)
0
2
0
Order By: Relevance
“…3 After removal of cases with missing data across each of the variables we describe below, all models are based on a sample size of 7,484 cases. Although underutilized by academics, FYSAS data have been used as the basis for a few published studies (e.g., Eitle, 2005; Meldrum & Piquero, 2015; Peleg-Oren, Cardenas, Comerford, & Galea, 2012; Peleg-Oren, Saint-Jean, Cardenas, Tammara, & Pierre, 2009). For additional information on the FYSAS survey and administration procedures, please refer to the website of the Florida Department of Children and Families and the 2017 FYSAS State Report.…”
Section: Methodsmentioning
confidence: 99%
“…3 After removal of cases with missing data across each of the variables we describe below, all models are based on a sample size of 7,484 cases. Although underutilized by academics, FYSAS data have been used as the basis for a few published studies (e.g., Eitle, 2005; Meldrum & Piquero, 2015; Peleg-Oren, Cardenas, Comerford, & Galea, 2012; Peleg-Oren, Saint-Jean, Cardenas, Tammara, & Pierre, 2009). For additional information on the FYSAS survey and administration procedures, please refer to the website of the Florida Department of Children and Families and the 2017 FYSAS State Report.…”
Section: Methodsmentioning
confidence: 99%
“…Self-report surveys are also one of the most widely used methods of collecting information on illicit drug use and, like offending, these behaviours are also prohibited, so the validity of data generated by these surveys is also often examined (for reviews, see Harrison, 1997; Richter and Johnson, 2001), with the majority of studies concluding that drug use is fairly accurately reported in self-report surveys. Reviews have suggested that drug use may have an impact on whether individuals correctly self-report their offending, with those who are criminally involved being less likely to accurately self-report, possibly because they would face the heaviest penalties (Harrison, 1997; Meldrum and Piquero, 2014).…”
Section: Validitymentioning
confidence: 99%